2013
DOI: 10.4103/2249-4863.117424
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in blood pressure, blood sugar, and cholesterol in young adults with comparable routine physical exertion

Abstract: Context:Gender differences in the risk of developing non-communicable diseases (NCD) are a matter of debate. The susceptibility of a woman to NCD should be evaluated taking into consideration the social factors that limit the physical activity among women. It will be interesting to note what will happen if women are allowed to take part in physical exercise to the extent of men.Aims:To find out the gender difference in the pattern of the clinical and biochemical indices related to NCD in young adults with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…It is well documented that the blood pressure is lower in females than that in age‐matched males . This notion is consistent with the recent observations reported in rodent models, indicating that females have a much higher parasympathetic activity than males and neuroprotective action of estrogen .…”
Section: Introductionsupporting
confidence: 91%
“…It is well documented that the blood pressure is lower in females than that in age‐matched males . This notion is consistent with the recent observations reported in rodent models, indicating that females have a much higher parasympathetic activity than males and neuroprotective action of estrogen .…”
Section: Introductionsupporting
confidence: 91%
“…The role that male versus female sex plays in the prevalence of NCDs is still a matter of debate. Many studies support the notion that the prevalence of NCDs differs according to sex [ 38 , 39 ]. A survey of subjects in middle- and low-income countries reported that male sex is a risk factor for NCDs [ 40 ].…”
Section: Discussionmentioning
confidence: 97%
“…The present findings were consistent with a past study conducted by Chee et al [ 39 ] among Malaysian employees. The plausible mechanism to explain these results is that the endogenous hormones of females are less atherogenic and therefore has lesser effect on insulin resistance, providing the protective effects towards MetS components [ 40 ].…”
Section: Discussionmentioning
confidence: 99%